Ben and Beatriz - Gamarra, Katalina (Graydon House, 2022)
"Beatriz Herrera is a fierce woman who will take you down with her quick wit and keen intellect. And after the results of the 2016 election worked hard to erase her identity as a queer biracial woman, she'd be right to. Especially if you come for her sweet BFF cousin, Hero. Beatriz would do anything for her, a loyalty that lands Beatriz precisely where she doesn't want to be: spending a week at the ridiculous Cape Cod mansion of stupid-hot playboy Ben Montgomery. The same Ben Montgomery she definitely shouldn't have hooked up with that one time... The things we do for family. White and wealthy, Ben talks the talk and walks the walk of privilege, but deep down, he's wrestling with the politics and expectations of a conservative family he can't relate to. Though Beatriz's caustic tongue drives him wild in the very best way, he's the last person she'd want, because she has zero interest in compromising her identity. But as her and Ben's assumptions begin to unravel and their hookups turn into something real, they start wondering if it's still possible to hold space for one another and the inescapable love that unites them"--